Pengaruh Brand Image Dan Harga Serta Atribut Produk Terhadap Keputusan Pembelian Sepeda Motor Merek Honda CBR 150CC Di Samarinda - Muhammad Hilmi Lingga Sabda KasiH; Tetra Hidayati; Herning Indriastuti (Fakultas Ekonomi Dan Bisnis Universitas Mulawarman, 2018)
Target of this research is to know and analyse influence of image brand, product attribute and price to decision of purchasing of Motorbike Brand of Honda CBR 150cc Samarinda. This Research represent research of kausal asosiatif by using approach of kauntitatif. Sampel the used consumer using brand motorbike of Honda CBR 150 cc in Samarinda. Sampel the used to amount to 100 consumer people. Analysis the used doubled linear regresi with program of SPSS version 15. Result of research of showed that proven image brand have positive influence and significant to decision of purchasing of brand motorbike of honda CBR 150cc in Samarinda, this matter seen from and body of desain very modern make responder come up self confidence. Result of research of showed that proven price have positive influence and significant to decision of purchasing of brand motorbike of honda CBR 150cc in Samarinda, this matter seen from proportionate price with motor specification and form and this enough reached by among society. Result of research of showed that proven product attribute have positive influence and significant to decision of purchasing of brand motorbike of honda CBR 150cc in Samarinda, this matter seen from machine very good, strength and durable and also motor component very complete as according to sport motor